Islamic ethics commitment and bank outcomes: Evidence in South East Asia - Arif Lukman Santoso; Fakarudin Kamarudin; Bany Ariffin Bin Amin Noordin; Wei Theng Lau (Cogent Economics & Finance, 2023)
Ethical values in corporations and businesses are inseparable. Religious norms revise the system and economic law as a code of ethics and discipline applied to solve moral problems in business. This study analyzes the disclosure of Islamic Ethics commitment in the annual report of Islamic banking in South East Asia and the effect on Bank Outcomes. Bank Outcomes in this study are financial performance and business risk during 2012-2019. This study used 29 full-fledged Islamic banks in Southeast Asia. The results showed that Islamic Ethics Commitment (IEC) positively affects financial performance, measured by return on asset (ROA). However, if ROE measures financial performance, IEC does not correlate. The IEC also negatively correlates with business risk measured by banks' liquidity and financing risk (Deposit to Asset ratio and Non-Performing Financing). The test is robust when financial performance is measured by banks' Net Interest Margin (NIM), and the financing-to-deposit ratio (FDR) measures business risk.
Keywords: 330; financial performance; Islamic Bank and business risk; Islamic ethical identity